2007
DOI: 10.1111/j.1399-6576.2007.01486.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self‐reported neuropathic pain and impact on quality of life: a prospective representative survey

Abstract: For the first time, data on the prevalence of NeP in Austria are available. Pain patterns in those affected are characteristic and impact on QOL as well as pain intensity are severe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
114
1
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(136 citation statements)
references
References 14 publications
10
114
1
11
Order By: Relevance
“…A 3.3% prevalence of neuropathic pain was reported in a study from Austria, in which the majority of subjects identified non-traumatic etiologies as the cause of the pain. 38 The exact prevalence of traumatic nerve injuries is difficult to determine. [39][40][41] Midha reported that 4,538 trauma patients were seen from January 1986 to December 1994 at a level 1 trauma centre in Ontario, Canada, including 60 patients with brachial plexus injuries.…”
Section: Discussionmentioning
confidence: 99%
“…A 3.3% prevalence of neuropathic pain was reported in a study from Austria, in which the majority of subjects identified non-traumatic etiologies as the cause of the pain. 38 The exact prevalence of traumatic nerve injuries is difficult to determine. [39][40][41] Midha reported that 4,538 trauma patients were seen from January 1986 to December 1994 at a level 1 trauma centre in Ontario, Canada, including 60 patients with brachial plexus injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain because of several factors, as a widespread problem, has been estimated to affect 19% of the European population [1,2]. Within this population, neuropathic pain (NP) is of particular interest because they have a greater comorbidity profile than age-and sex-matched controls.…”
Section: Introductionmentioning
confidence: 99%
“…Pada kelompok farmakologi ini, mereka menganggap pendekatan farmakologi lebih baik bila dibandingkan pendekatan lain dalam mengurangi rasa nyeri. Hal ini tentu saja berdampak pada kualitas kesehatan pasien yang berdampak pada rendahnya kualitas hidup pasien dengan nyeri kronis (Gustorff, Dorner, Likar, Grisold, Lawrence, Schwarz, & Rieder, 2008;Otto, Bach, Jensen, & Sindrup, 2007;Vasudevan, 2004).…”
Section: Diskusiunclassified